Analisis Pelaksanaan Projek Penguatan Profil Pelajar Pancasila pada Anak Usia Dasar - Hidayat, Nurul; Nuri Satriyawan, Aziz; Agustinna, Ira (IBTIDA', 2025)
In order to ensure a project runs well, a good contribution is also needed in developing student competence through Pancasila values. The aim of this research is to analyze the implementation of the project to strengthen the profile of Pancasila students (P5) at MIN 7 Ngawi in class 1 B. This qualitative research uses interview sheets, observation and documentation as well as field notes as research instruments. Data analysis techniques use source triangulation and technical triangulation. The subjects of this research were the Principal, Class 1B Teacher, and Class 1B students totaling 19 children. The results of this research show that the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) at MIN 7 Ngawi went well and optimally because of the planning of the facilitator team and also the role of teachers in guiding students in making the project. Implementation of P5 for class 1 B students is carried out by making works using used materials, class decorations, souvenirs and so on. Through this P5 activity, students are also instilled with the spirit of independence, creativity and entrepreneurship through making works that have use and selling value such as decorations and souvenirs and finally evaluation and reflection as material for development in subsequent learning. Keywords: Analysis of P5 Implementation, Elementary School